MR‐based detection of individual histotripsy bubble clouds formed in tissues and phantoms. Issue 5 (24th November 2015) - Allen, Steven P.; Hernandez‐Garcia, Luis; Cain, Charles A.; Hall, Timothy L.
Abstract : Purpose: To demonstrate that MR sequences can detect individual histotripsy bubble clouds formed inside intact tissues. Methods: A line‐scan and an EPI sequence were sensitized to histotripsy by inserting a bipolar gradient whose lobes bracketed the lifespan of a histotripsy bubble cloud. Using a 7 Tesla, small‐bore scanner, these sequences monitored histotripsy clouds formed in an agar phantom and in vitro porcine liver and brain. The bipolar gradients were adjusted to apply phase with k‐space frequencies of 10, 300 or 400 cm −1 . Acoustic pressure amplitude was also varied. Cavitation was simultaneously monitored using a passive cavitation detection system. Results: Each image captured local signal loss specific to an individual bubble cloud. In the agar phantom, this signal loss appeared only when the transducer output exceeded the cavitation threshold pressure. In tissues, bubble clouds were immediately detected when the gradients created phase with k‐space frequencies of 300 and 400 cm −1 . When the gradients created phase with a k‐space frequency of 10 cm −1, individual bubble clouds were not detectable until many acoustic pulses had been applied to the tissue. Conclusion: Cavitation‐sensitive MR‐sequences can detect single histotripsy bubble clouds formed in biologic tissue. Detection is influenced by the sensitizing gradients and treatment history. Magn Reson Med 76:1486–1493, 2016. © 2015 International Society for Magnetic Resonance in Medicine